Time Spent on Homework: Correlations Between Parents’ and Teachers’ Perceptions and Children’s Performance - Šilinskas, Gintautas; Raižienė, Saulė (Psichologija, 2024)
This study investigated differences in teachers’ and parents’ perceptions about homework and their correlations with children’s achievement in Grade 4 – the end grade for primary school in Lithuania. Data were collected at the end of Grade 4 (February–March 2024). Teachers (n = 39) answered online questionnaires on homework frequency and expected homework time; parents (n = 525) completed paper questionnaires about homework frequency, time, and help. Children (n = 576) completed tests measuring literacy and math skills, and school administrations provided children’s Grade 4 grades and results from national standardized testing. Most parents and teachers reported that homework was assigned daily. Teachers reported that children should spend around one hour daily on homework; parents reported children spending on average one hour and ten minutes daily on homework and a great variation in the amount of weekly homework help children received. Compared to teachers, parents reported more frequent homework and more homework time. Only parental reports of time spent and help received for homework significantly correlated to children’s academic performance measures, albeit negatively. Overall, parents and teachers perceived homework time differently. Additionally, the less well Grade 4 students did academically, the more time they spent on homework, and the more help they required from family.
Keywords: homework; homework frequency; homework time; homework help; academic performance